Analisis Strategi Digital Marketing dalam Meningkatkan Kepercayaan Muzakki di Lembaga Amil Zakat Lidzikri Rancasari Kota Bandung - Atsdar, Donni; Suryaman, Maman (Masyarakat Ekonomi Syariah Bogor, 2024)
This research analyzes digital marketing strategies in increasing muzakki's trust in the lidzikri zakat amil institution using descriptive qualitative research methods, where the research focus is on digital marketing programs implemented by the lidzikri zakat amil institution in increasing muzakki's trust in giving zakat. This research method is descriptive qualitative, with data collection techniques through interviews, observation, documentation studies and literature studies. The types of data used in this research are primary data and secondary data. The results of this research are that the Amil Zakat Lidzikri institution uses a digital marketing strategy with SMO (social media optimization) and SMM (social media marketing) methods, namely the use of social media platforms such as websites, Instagram, Facebook and WhatsApp, and other programs. The general ones that have been implemented are educational programs, economic programs, social programs and health programs.